2012
DOI: 10.1021/jf303374g
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Markers of Shiikuwasha Juice Adulterated with Calamondin Juice

Abstract: Detection of shiikuwasha (Citrus depressa Hayata) juice adulterated with calamondin (Citrus madurensis Lour.) juice was investigated by the analyses of (1) phloretin dihydrochalcone glucoside, 3',5'-di-C-β-glucopyranosylphloretin (PD) detected by thin-layer chromatography and high-performance liquid chromatography (HPLC), (2) polymethoxylated flavones (PMFs), included nobiletin, tangeretin, and sinensetin, detected by HPLC, and (3) γ-terpinene peak percentage obtained by headspace solid-phase microextraction g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…These equations were useful for confirming the presence or absence of small amounts (1%) of shiikuwasha juice in calamondin juice. Yamamoto et al (2012) reported γ-terpinene as a chemical marker to detect adulterated shiikuwasha juice. In this study, γ-terpinene and linalool were shown to be new and useful chemical markers for detecting small amounts of shiikuwasha juice in calamondin juice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These equations were useful for confirming the presence or absence of small amounts (1%) of shiikuwasha juice in calamondin juice. Yamamoto et al (2012) reported γ-terpinene as a chemical marker to detect adulterated shiikuwasha juice. In this study, γ-terpinene and linalool were shown to be new and useful chemical markers for detecting small amounts of shiikuwasha juice in calamondin juice.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, shiikuwasha juice adulterated with calamondin juice is difficult to detect. Yamamoto et al (2012) reported the use of 3′,5′-di-C-β-glucopyranosylphloretin, polymethoxylated flavones and γ-terpinene in detecting shiikuwasha juice adulterated with calamondin juice. Although the chemical characteristics of both citruses were revealed, differences in sensory characteristics have not been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…1. [25]. In addition, HAE extracts contained vitamin C at a very lower percentage than in INEFU extracts (range 0.12~0.23%).…”
Section: Identification and Quantification Of Vitamin C In Citrus Madmentioning
confidence: 87%
“…[11]. Calamondin orange (Citrus madurensis, Citrofortunella microcarpa), which belongs to Citrus Metacitrus Pseudofortunella, ranges from tropical to subtropical areas, including China, Philippines, Central America, Japan, and Hawaii [12]. Calamondin orange contains vitamin C, including tangeretin, and sinensetin, in large quantities in the peel part of this citrus orange [13].…”
Section: Introductionmentioning
confidence: 99%
“…These compounds are also reported to be present in high levels in the fruits of Shiikuwasha (Citrus depressa) and Calamondin (Citrus madurensis). 18,19 In recent years, advances in chromatographic techniques have led to improved methods for the rapid separation and isolation of bioactive compounds. Simultaneously separation and spectroscopic detection methods, termed hyphenated chromatography, can be used to elucidate the tentative identity of the compounds of interest.…”
Section: ■ Introductionmentioning
confidence: 99%